The bonding effect of money in the workplace: priming money weakens the negative relationship between ostracism and prosocial behaviour. Issue 2 (3rd March 2016) - Mok, Aurelia; De Cremer, David
Abstract : The feeling of being ostracized in the workplace has been associated with the withdrawal of prosocial and helping behaviours. We propose that reminders of money would moderate (weaken) this relationship. We conducted three studies with working adult participants. Results showed that activating thoughts of money, even unrelated to compensation, reduced the negative relationship between ostracism and prosocial intentions (Studies 1 and 3) and behaviour (Study 2) in the organization. Study 3 furthermore showed that this effect occurs by reinforcing organizational identification. Our research identifies a factor that is already present in the work setting that could buffer the negative psychological and behavioural outcomes associated with ostracism: cues of money. We discuss the implications for research on money, social threats, and organizational behaviour.